ANALISIS FAKTOR YANG MEMPENGARUSI MASYARAKAT SEKITAR MENJADI TENAGA KERJA DI PONDOK (STUDI PADA PEKERJA PONDOK MODERN DARUSSALAM GONTOR KAMPUS 6 MAGELANG) - Ahmad Hariri Zadi; Imam Haryadi (Universitas Darussalam Gontor, 2021)
The purpose of this study is to find out what factors influence the community to become workers in the cottage, and to find out the most influential factors to become workers. This research is a field research, using descriptive qualitative. The population was all 79 employees of PM Gontor Campus 6 Magelang, with a sample of 18 people. Purposive sampling method is used to get data from people who know best. The method of data collection uses the method of observation, interviews, documents, and triangulation. The results of this study show that there are 4 factors that influence the community to become workers in the cottage, namely: Religiosity, Security, Leisure, and social. And the most influential factor is the factor of religiosity. The people who have worked in the hut so that istiqomah works in order to get blessings. Because work does not only seek the life of the world, but also for the hereafter.